Green Minimalistic Approach to Synthesize Chitosan-Based Durable Polymer Hydrogel Materials for Supporting Cell Growth - Justyna Pawlik; Klaudia Borawska; Piotr Wieczorek; Kamil Kamiński (Gels, 2025)
In this work, we present an innovative, crosslinker-free method for preparing chitosan-based hydrogel precursors, fully aligned with green chemistry principles and composed of only five non-toxic, readily available reagents. The key novelty lies in the use of glycerin, which, during thermal annealing, evaporates and triggers a surface or bulk chemical transformation of chitosan, depending on its concentration. This process significantly enhances the material’s mechanical properties after swelling—with up to a 35% increase in tensile strength and a notable reduction in water uptake compared to systems containing AMPS-based crosslinkers. FTIR analysis indicates a partial re-acetylation of chitosan, shifting its structure toward that of chitin, which correlates with improved hydrophobicity (as shown by increased contact angles up to 92°) and greater structural integrity. These improvements are particularly pronounced at glycerin concentrations of 10–20%, whereas higher concentrations (50%) result in brittle, non-moldable films. Importantly, preliminary biological tests confirm that the resulting hydrogels are effectively colonized by mammalian cells, making them promising candidates for bioimplant or tissue engineering applications. Surface morphology and compatibility were further assessed via SEM, AFM, and contact angle measurements.